USING ROBOTICS AND ENGINEERING DESIGN INQUIRIES TO OPTIMIZE MATHEMATICS LEARNING FOR MIDDLE LEVEL TEACHERS: A CASE STUDY - Chahine, Iman Chafik; Robinson, Norman; Mansion, Kimbeni (Journal on Mathematics Education, 2020)
This exploratory case study reports findings on 20 middle-level science and mathematics teachers’ perceptions of the effectiveness of a one-year project in which teachers engaged in using robotics and engineering design inquiries in their classrooms. Principled by Bandura’s Social Learning Theory (SLT) and using mixed methods approaches, the study measured teachers' efficacy through the Mathematics Teaching Efficacy Belief Instrument (MTEBI) and observation logs before and after the program. The results of this study showed statistically significant differences between PRE MTEBI and POST MTEBI scores. Furthermore, five themes emerged that illuminated potential affordances and constraints that teachers perceive as opportunities and barriers to employing robotics and design thinking in the mathematics/science classrooms. The reported themes are creating collaborative spaces underpinned by design thinking affords transformative learning; problem-solving through shared inquiry elevates confidence; building connections between mathematical concepts and real-life phenomenon supports a willingness to learn new ideas; system support, resources, and funding are prerequisites to engage in modeling design; and designated curriculum restrains teachers from engaging in extra activities that focus on design thinking.